2005
DOI: 10.1002/eji.200535053
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of cytotoxic T lymphocytes is a functional constraint maintaining HIV-1 Nef expression

Abstract: Nef expression is not required for HIV-1 replication and is highly targeted by CD8 + CTL, raising the question of why Nef expression is not lost in order to evade immunity in vivo. We explore whether MHC class I (MHC-I) down-regulation to evade CTL in general is a selective pressure maintaining Nef. HIV-1 with functional Nef (wild type, WT) is compared to virus containing a Nef point mutation (M20A) that selectively ablates MHC-I down-regulation. WT-infected cells are relatively resistant to cytolysis and less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…However, the suppression of MHC-I upregulation suggests a potent deficiency in initiating the adaptive response. Suppression of antigen presentation by MHC-I is employed by multiple virus types to evade immune clearance, thereby promoting persistent infections (1,2,5,6,18,51,61). The identification of viral antigen in the brains of NiV encephalitis patients postmortem indicates the spread of the virus past the presumed respiratory route of entry (13,27).…”
Section: Discussionmentioning
confidence: 99%
“…However, the suppression of MHC-I upregulation suggests a potent deficiency in initiating the adaptive response. Suppression of antigen presentation by MHC-I is employed by multiple virus types to evade immune clearance, thereby promoting persistent infections (1,2,5,6,18,51,61). The identification of viral antigen in the brains of NiV encephalitis patients postmortem indicates the spread of the virus past the presumed respiratory route of entry (13,27).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the early-killing phenomenon first described by Sacha et al (5) varies, depending on the virus inoculum, and that CTLs targeting different epitopes require different amounts of input virus to achieve early killing (28). Our earlier data obtained with a virus suppression assay have suggested that most Gag-specific CTLs are susceptible to Nef (10,11,21). In these assays, a low initial inoculum of virus is allowed to spread, and thus the dose of virus for each infected cell is unclear in comparison to controlled single-round infections such as those used by Sacha et al (5).…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, a version of HIV-1 Nef containing the Gag SL9 epitope was created through substitution mutations between residues 40 and 55 of Nef. Epitope mutations known to disrupt CTL recognition were generated in the p83-2.1 Gag reading frame by site-directed mutagenesis (Agilent Technologies), and the M20A mutation, which ablates HLA-I downregulation by Nef (20,21), also was generated by site-directed mutagenesis in plasmid p83-10. (Table 2) containing the murine CD24 reporter gene in the vpr locus, followed by flow cytometric analysis as previously described (18,21).…”
Section: Hiv-1-permissive Target Cell Lines the Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Though, direct effects of HIV on CD8+ population and its function(s) are also reported. HIV is known to manipulate the expression of MHC class I using Nef expression and in turn evade the CTL response [72,73]. Nef is also known to downregulate the expression of CD80 and CD86 on infected cells, which leads to defective priming, activation, and further the function of CD8+ CTL cells [66].…”
Section: T Cellsmentioning
confidence: 99%